Eksplorasi Metode Geolistrik Resistivitas: Studi Kasus Zona Sesar Utama Manado dan Akuifer Air Tanah Di Kabupaten Minahasa Utara - As'ari, As'ari; Tongkukut, Seni Herlina Juita; Suoth, Verna Albert; Panjaitan, Sarmaria; Akasi, Iftita Anugraini; Pulu, Meidy Rosalie (Jurnal MIPA, 2022)
The Manado Fault is a fault located in North Sulawesi which is through the North Minahasa Regency. The fault area is a weak zone that is formed when a crack occurs on the earth's surface, a gap with a certain depth and width is formed, because the natural process of the gap is filled by the surrounding soil material. This weak zone has the potential to become a reservoir for rainwater, which can become a groundwater aquifer. The formation of fractures depends on the geology of an area, fracture characteristics such as the width and depth of the fracture affect the potential for groundwater stored as aquifers. This study aims to identify the influence of geology on the physical parameters of the fault that determine the potential presence of groundwater aquifers in North Minahasa Regency. The faults identified as fractures in Watutumou II Village, Kalawat District and Rap Rap Village, Airmadidi District, North Minahasa Regency are associated with fluids and form groundwater aquifers. The potential for groundwater storage is related to geological conditions following the trend of depth to fracture width with a gradient of -0.0588.